2020
DOI: 10.1055/a-1212-2930
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyketides Isolated from the Endophytic Fungus Phomopsis sp. CAM212 with a Semisynthetic Derivative Downregulating the ERK/IκBα Signaling Pathways

Abstract: Three previously undescribed natural products, phomopsinin A – C (1 – 3), together with three known compounds, namely, cis-hydroxymellein (4), phomoxanthone A (5) and cytochalasin L-696,474 (6), were isolated from the solid culture of Phomopsis sp. CAM212, an endophytic fungus obtained from Garcinia xanthochymus. Their structures were determined on the basis of spectroscopic data, including IR, NMR, and MS. The absolute configurations of 1 and 2 were assigned by comparing their experimental and calculated ECD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The increase in efficacy observed during the tests suggests that the compounds' constituents may act synergistically on single or multiple targets associated with the physiological process leading to the destruction of E. histolytica trophozoites. Previously published work demonstrated that the use of phomopsinin A acetate obtained after acetylation of phomopsinin A significantly increased the activity of the acetylated compound in the nitric oxide assay in LPSstimulated RAW 264.7 macrophages [30]. E. coli bacillary dysentery due to its various pathotypes remains a global public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in efficacy observed during the tests suggests that the compounds' constituents may act synergistically on single or multiple targets associated with the physiological process leading to the destruction of E. histolytica trophozoites. Previously published work demonstrated that the use of phomopsinin A acetate obtained after acetylation of phomopsinin A significantly increased the activity of the acetylated compound in the nitric oxide assay in LPSstimulated RAW 264.7 macrophages [30]. E. coli bacillary dysentery due to its various pathotypes remains a global public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…2 Fungi in the genus Xylaria have been extensively investigated and different classes of bioactive compounds have been isolated, such as antimalarial, 3 cytotoxic, 4,5 antimicrobial, 6 anti-HIV, 7 antioxidant, 8 phytotoxic, [9][10][11] and immunosuppressive metabolites. 12 In our continuous search for secondary metabolites with biological importance from natural sources, [13][14][15] we have carried out studies on a fungal strain Xylaria sp. originally isolated from the leaves of G. polyantha collected in Cameroon.…”
mentioning
confidence: 99%